A study on the integration of interior architecture in selected malls in Quezon City - Alcanices, Arne Lorraine A.; Mayo, Adelaida Villaraza (2007)
This study sought to determine whether or not the philosophy of Interior Architecture was applied on the selected shopping malls in Quezon City. It determined whether the elements and principles of design found in the architecture of the mall are consistent with its interiors. It also analyzed the interior design of the mall according to the parameters of the philosophy of interior architecture. The researcher used the descriptive survey method and employed purposive sampling in selecting the two malls included in the study. Literary research, photographic documentation, ocular inspections, and thorough observations were done in order to gather the necessary data. Data treatment utilized content analysis in order to determine whether the two selected malls followed the philosophy of interior architecture. Findings indicated that Mall A and Mall B met the parameters of interior architecture set by the researcher. The set parameters were the third-dimension, the fourth dimension, lighting, color, and furniture. Results showed that the design of the exterior is consistent with the interior in both malls based on the parameters of interior architecture. All A adopted the concept of a "kaleidoscope" while Mall B integrated the attributes of an "ice block" from which the designs took inspirations. The study confirmed that Mall A and B applied the philosophy of interior architecture.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Interior architecture; Shopping malls -- Decoration -- Philippines